Impactos do funk na vida dos funkeiros : reconhecimento na interação intragrupo; estigmatização e discriminação na relação extragrupo - Mendonça, Vanderlei Cristo (2012)
This dissertation aims to present the dual social role that the "identity funkeira" plays in the lives of young people that if autointitulam "funkers". With this aim, to identify the processes that pervades the intra-group interactions of funkers the light of the Theory of recognition in the perspective of theoretical Axel Honneth. This approach has allowed us to reach the adequate understanding of the interaction inside of groups of funkers, perceiving, inclusive, as they are heavily steeped in by processes of recognition. On the other hand, using the advances of sociological theory and social psychology, with regard to the questions on the poor and poverty in Brazil, it was contended the hypothesis that the symbols that characterize this musical genre they bring in their swelling characteristics that make fall on the funkers prejudices which, in Brazilian society, mark the poverty and the poor. The analysis took into consideration, still, the context of the sensation of fear and insecurity from which is has justified certain postures of search for security which dispenses with the identification of the subject of crime, that is, the identification of the "enemy contemporary social", that, in dialectical process, it strengthens the stigmatisation of funkeiro.